PENGARUH NILAI UTILITARIAN DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP KEPUASAN UNTUK MENINGKATKAN NIAT BELI ULANG (Studi pada Pengguna Aplikasi E-Money Merek OVO di Kota Denpasar dan Kabupaten Badung) - Charisma, Lady; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen; Vol 9 No 6 (2020), 2020)
The purpose of this study is to determine the effect of utilitarian value and perceived ease of use on satisfaction to increase repurchase intentions. The study was conducted in Denpasar City and Badung Regency involving 104 respondents who met the criteria based on purposive sampling technique. The questionnaire was tested on 30 respondents in advance to find out the accuracy and consistensy of the questionnaire through validity and reliability tests. Furthermore, the overall data received was analyzed using multiple regression analysis and simple regression analysis. The results found that utilitarian value and perceived ease of use have a positive and significant effect on satisfaction, satisfaction has a positive and significant effect on repurchase intention, and utilitarian value is the most variabel that affected the satisfaction. Keywords : utilitarian i value, perceived i ease of i use, satisfaction, repurchase i intentio n